Promoting Gender Sensitivity in Social Work - Henriksen, Ann-Karina (Kvinder, Køn & Forskning, 2017)
The article reflects on teaching gender theory to students who are not enrolled in a gender programme. It argues that learning can be facilitated to social work students by tapping into their own gendered experiences and by linking gender to wider concerns about social inequality. The article draws on personal notes from teaching gender and social diversity to social work students. In this context, two main obstacles are identified: anti-feminism and individualization. These obstacles can be addressed productively. First by bringing students’ gendered experiences and social categorisations into play, and second, by demonstrating how social problems are shaped by gender structures and unequal power relations.